2018
DOI: 10.1002/jcb.27129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate aberrantly methylated and differentially expressed genes in thyroid cancer

Abstract: Aberrant methylation of DNA sequences plays a criticle role in finding novel aberrantly methylated genes and pathways in thyroid cancer (THCA). This study aimed to integrate three cohorts profile datasets to find novel aberrantly methylated genes and pathways in THCA. Data of gene expression profiling microarrays (GSE33630 and GSE65144) and gene methylation profiling microarrays (GSE51090) were downloaded from the Gene Expression Omnibus database. Aberrantly methylated and differentially expressed genes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…SPP1 enhances CRC metastasis through activation of epithelial mesenchymal transition (EMT) 46. SPP1 was also found to be an aberrantly methylated hub gene that might participate in the progression and development of thyroid cancer (THCA) 47. SPP1 DNA methylation was significantly negatively correlated with SPP1 mRNA expression in THCA 47; it was hypomethylated and highly expressed in THCA 47.…”
Section: Discussionmentioning
confidence: 99%
“…SPP1 enhances CRC metastasis through activation of epithelial mesenchymal transition (EMT) 46. SPP1 was also found to be an aberrantly methylated hub gene that might participate in the progression and development of thyroid cancer (THCA) 47. SPP1 DNA methylation was significantly negatively correlated with SPP1 mRNA expression in THCA 47; it was hypomethylated and highly expressed in THCA 47.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of laboratory research, bioinformatics studies as well as meta-analyses have shown that OPN levels can also be considered as a biomarker for diagnosis or as a predicting tool for patient clinical outcome in several types of cancer, such as lung adenocarcinoma, esophageal carcinoma, prostate cancer, melanoma, and colorectal adenocarcinoma. Its expression levels are considered useful for predicting responses to anti-EGFR therapy in patients with triple-negative breast cancer and as a methylation-based biomarker for precise diagnosis and treatment for thyroid cancer [96,97,98,99,100,101,102].…”
Section: Reviewmentioning
confidence: 99%
“…The Search Tool for the Retrieval of Interacting Genes (STRING, version 10.5) database () provides both experimental and predicted interaction information (20). A PPI network of DEGs was constructed with STRING to further evaluate the molecular mechanism of cellular processing.…”
Section: Methodsmentioning
confidence: 99%